Religious Commodification through Hadis of Siwak and its Halal Branding: Unity of Sciences Perspective - Kurnia Muhajarah; Moh. Erfan Soebahar; Noor Safuan Che Noh; Ali Muhtarom; Silvia Riskha Fabriar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This research is motivated by the idea that commodification is a process of changing the value of a product which previously only had a use value and then becomes an exchange value where the demand for the product is determined by the price, designed by the manufacturer. The formulation of the research problem is how to commodify the religion of siwak products through halal labels and how to analyze media and advertisements related to the religious commodification of siwak products. The research method is libraryresearch. The results showed that currently siwak has turned into toothpaste. Toothpaste has become one of the people's daily needs. The habit of brushing teeth has existed since ancient times and people prefer to use siwak wood. Currently there are several toothpaste products that offer halal products, which contain the siwak content taught by the Prophet Muhammad and have a halal certificate from Indonesian Ulama Council. From the realm of media, technological, media and economic developments play an important role in thereligious commodification. This is also one way of advertising by playing with the psychology of viewers by choosing halal products, it will show high faith.